Are You Marrying the Right Person? Healthy Signs and Red Flags - LuAnn Duncan; Victor W. Harris (EDIS)
This document explores the importance of recognizing healthy relationship patterns and red flags before marriage. It introduces Dr. John Van Epp’s model, which outlines five key steps: knowing, trusting, relying, committing, and physical intimacy. The article emphasizes the need for these steps to progress sequentially to ensure a strong foundation. Additionally, it provides a checklist of 25 red flags to help individuals identify potential issues in their relationships. The goal is to help readers make informed decisions about their partners and build healthy, lasting relationships. Original publication date August 2012.